Porphyrin/Platinum(II) C^N^N Acetylide Complexes: Synthesis, Photophysical Properties, and Singlet Oxygen Generation. Issue 12 (5th February 2016) - Jana, Atanu; McKenzie, Luke; Wragg, Ashley B.; Ishida, Masatoshi; Hill, Jonathan P.; Weinstein, Julia A.; Baggaley, Elizabeth; Ward, Michael D.
Abstract: A new class of substituted porphyrins has been developed in which a different number of cyclometalated Pt II C^N^N acetylides and polyethylene glycol (PEG) chains are attached to the meso positions of the porphyrin core, which are meant for photophysical, electrochemical, and in vitro light‐induced singlet oxygen ( 1 O2 ) generation studies. All of these Zn II porphyrin–Pt II C^N^N acetylide conjugates show moderate to high ( Φ Δ =0.55 to 0.63) singlet oxygen generation efficiency. The complexes are soluble in organic solvents but, despite the PEG substituents, slowly aggregate in aqueous solvent systems. These conjugates also exhibit interesting photophysical properties, including near‐complete photoinduced energy transfer (PEnT) through the rigid acetylenic bond(s) from the Pt II C^N^N antenna units to the Zn II porphyrin core, which shows sensitized luminescence, as shown by quenching of Pt II C^N^N‐based luminescence. Electrochemical measurements show a set of redox processes that are approximately the sum of what is observed for the Pt II C^N^N acetylide and Zn II porphyrin units. UV/Vis spectroscopic properties are supported by DFT calculations. Abstract : The photophysical, electrochemical, and light‐induced singlet oxygen ( 1 O2 ) generation properties are reported for a series of Zn II porphyrin/Pt II C^N^N acetylide compounds. One, two, or three cyclometallated Pt II C^N^N luminophores are grafted onto a Zn II porphyrin core (see figure; R=PEG chain).